The Effect of Inherent Supervision on Work Discipline Employees at Regional Income Management Agency of Asahan District - Khairi, Bayu; Sihombing, R. Sally Marisa (Budapest International Research and Critics University, 2022)
The purpose of this study was to analyze the effect of inherent supervision on the work discipline of employees at the Regional Income Management Agency of Asahan Distict. This research design uses associative research with quantitative methods. The population and sample used are all civil servants at the Regional Income Management Agency of Asahan Distict with a total of 76 employees. The research instrument used was a questionnaire and the determination of the score using a Likert scale. The data analysis technique is through the Structural Equation Modeling model through the Partial Least Squares (PLS) application. The results of the research obtained are that inherent supervision has a score of 3.51 and is included in the high-level category, work discipline is included in the high-level category because it has a score of 3.48. Inherent supervision has a positive effect on work discipline. The T-statistic value obtained is 118.648 and the T-table value is 1.67, then T-statistic>T-table (118.648>1.67) and a significance value of 0.000, this means that the hypothesis can be accepted. The accepted hypothesis explains that the inherent supervision variable has a positive and significant effect on employee work discipline at the Regional Income Management Agency of Asahan Distict. The value of R Square in this study is 0.919 explaining the influence of inherent supervision on employee work discipline at the Regional Income Management Agency of Asahan Distict is 91.9%.